2008
DOI: 10.1111/j.1467-6486.2008.00812.x
|View full text |Cite
|
Sign up to set email alerts
|

HRM and Performance: A Plea for Reflexivity in HRM Studies

Abstract: In this Counterpoint, we build on Paauwe's suggestions to take the field of HRM and Performance further. Rather than aiming for a synthesis or proposing a radical alternative, we argue that R(econstructive)-reflexivity is needed for theorizing HRM. In particular, we bring in insights from critical studies on the notion of HRM, on the notion of performance, and on the theoretical relationship between them as a way to open up new research avenues and lines of interpretation. For each of these three aspects, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
128
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(138 citation statements)
references
References 65 publications
3
128
0
7
Order By: Relevance
“…However, the limitations of the managerialist agenda of HRM research have recently become the subject of considerable concern among mainstream HRM researchers (Boxall et al, 2007;Paauwe, 2009), while Critical HRM scholars (Delbridge and Keenoy, 2010;Keegan and Boselie, 2006) have continued to draw attention to the narrowness and conservatism of this mainstream. The main criticisms have been the obsession with linking HRM and business performance, an unreflexive acceptance of the managerialist perspective, assumptions of unitarism and universalism, the decontextualization of management practices, and the dominance of positivist approaches (see Delbridge and Keenoy, 2010;Hesketh and Fleetwood, 2006;Janssens and Steyaert, 2009;Keegan and Boselie, 2006;Keenoy, 2009).…”
Section: Current Issues Within Hrm Researchmentioning
confidence: 99%
“…However, the limitations of the managerialist agenda of HRM research have recently become the subject of considerable concern among mainstream HRM researchers (Boxall et al, 2007;Paauwe, 2009), while Critical HRM scholars (Delbridge and Keenoy, 2010;Keegan and Boselie, 2006) have continued to draw attention to the narrowness and conservatism of this mainstream. The main criticisms have been the obsession with linking HRM and business performance, an unreflexive acceptance of the managerialist perspective, assumptions of unitarism and universalism, the decontextualization of management practices, and the dominance of positivist approaches (see Delbridge and Keenoy, 2010;Hesketh and Fleetwood, 2006;Janssens and Steyaert, 2009;Keegan and Boselie, 2006;Keenoy, 2009).…”
Section: Current Issues Within Hrm Researchmentioning
confidence: 99%
“…Although strategic HRM researchers implicitly assume employees to be passive recipients of HRM (Janssens & Steyaert, 2009;Lepak & Boswell, 2012), other streams of literature have shown that this assumption is open to question. In fact, several concepts exist in the literature that capture the involvement of employees in HRM processes.…”
Section: Existing Conceptualizations Of Employee Actions In Hrm Procementioning
confidence: 99%
“…Although these studies help to advance our understanding of how employees perceive HRM systems, at the same time, several authors have raised concerns that they are too management-centered (Janssens & Steyaert, 2009;Keegan & Boselie, 2006;Lepak & Boswell, 2012). Prior research has primarily focused on managerial actions in HRM implementation, ignoring employees as important implementers of HRM systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these studies often employ a quantitative research design, including a preselected and limited set of variables in their models. Although the psychological lens is shown to be fruitful in order to answer many problem definitions at the micro-level, due to their intention to be parsimonious and internally consistent, the wider organizational context influencing and explaining how EP&Ps are perceived, attitudes shaped, and behaviours enacted is sometimes recognised, but often ignored and eliminated (cf., Janssens & Steyaert, 2009;Poole & Van de Ven, 1989). In practice, the employability issue is strongly embedded in political debates, and affected by global economic structures.…”
Section: Theoretical Framework the Merits Of A Process Approach To Pamentioning
confidence: 99%